ESTABLISHING THE FINANCIAL FOUNDATION OF THE CREDIT SECTOR IN THE FAR NORTH REGIONS WITHIN THE FRAMEWORK OF REGIONAL FINANCIAL SECURITY - Roman V. Badylevich; Elena A. Verbinenko (Север и рынок: формирование экономического порядка)
This study aims to analyze the sufficiency and sustainability of financial resource mobilization by credit institutions in the Far North regions of Russia within the framework of regional financial security assessment. The paper examines the adequacy of financial resource mobilization through coefficient analysis. It was found that, over the past decade, there has been a consistent increase in the attraction of funds by the credit system in the Far North regions, aligning with the national growth rates. In recent years, the rate of fund mobilization from legal entities has exceeded the national average, while the rate from individuals has been lower than Russia’s average. Currently, the Far North regions’ high financial potential is supported by a relatively high share of individual deposits.